Design of a Web-based Livestock Feed Sales Information System (Case Study of Lukman Jaya Store): Rancang Bangun Sistem Informasi Penjualan Pakan Ternak Berbasis Web (Studi Kasus Toko Lukman Jaya) - Witno, Kasaifi Al Qurdhowi Bin; Eviyanti, Ade; Rosid, Mochamad Alfan (Universitas Muhammadiyah Sidoarjo, 2023)
Lukman Jaya Store is business engaged in the sale of chicken feed and duck feed for both layer and broilers, and chicken / duck breeds. This shop in located in singkalan village RT14 RW06, Balongbendo district, Sidoarjo regency. The purpose of this research is to design a website-based livestock feed sales information system. The system used at lukman jaya stores is still manual, where the media for promotion is only throught banners and stories from one customer to another. The analysis of the system used is media observation, interviews and literature study. The results of this study are to make it easier for customers to buy and know the chicken and duck feed available at the Lukman Jaya Store.